2020
DOI: 10.29392/001c.14600
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in Nigeria: understanding COVID-19 transmission dynamics and immune responses

Abstract: There is a global rise in the emergence of infectious diseases and the enigmatic coronavirus disease 2019 (COVID-19) being the most recent one. It is ravaging the world with little understanding of its etiology and factors affecting its transmission dynamics. Meanwhile, seasonal variations in weather are major factors impacting infectious disease transmission patterns. Developing countries are likely to be most affected by weather changes that could impact on the spread and control of infectious diseases. In N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This study also focused on the governmental and nongovernmental engagement and the partnership, providing good results regarding the fight of COVID-19. Moreover, the authors in [54] examined the measures taken in Nigeria to fight the spread of COVID-19. The study indicated that vitamin D improves the immunity in COVID-19 patients.…”
Section: Discussion and Interpretationsmentioning
confidence: 99%
“…This study also focused on the governmental and nongovernmental engagement and the partnership, providing good results regarding the fight of COVID-19. Moreover, the authors in [54] examined the measures taken in Nigeria to fight the spread of COVID-19. The study indicated that vitamin D improves the immunity in COVID-19 patients.…”
Section: Discussion and Interpretationsmentioning
confidence: 99%
“…Because of many unknowns, a partial understanding of COVID-19 transmissibility has fueled the level of concern among the public health community, as most modeling suggests that the severity of the illness is more like influenza than SARS [4,11]. Similar to this is the fold of research affirming semblance of certain flu-like symptomatic features that COVID-19 shares with influenza [12], suggesting in this light the potentiality of mitigating factors on influenza being equally appropriate for quelling COVID-19. The development efforts to curtail the spread from hotspot to hotspot fervently proved abortive.…”
Section: Introductionmentioning
confidence: 99%
“…According to [8], the transmissions of most other human coronaviruses that result in mild respiratory symptoms, such as OC43 (HCoV-OC43) and HCoV-HKU1 spread rapidly based on seasonal variations. The seasonality of such viruses has been modelled to determine long-term simulation of the transmission of SARS-CoV-2 [9]. The geospatial modelling technique is an essential tool in examining the spatial distribution of most infectious diseases [10].…”
Section: Introductionmentioning
confidence: 99%